2008
DOI: 10.1038/nature07289
|View full text |Cite
|
Sign up to set email alerts
|

Control of plant germline proliferation by SCFFBL17 degradation of cell cycle inhibitors

Abstract: Flowering plants possess a unique reproductive strategy, involving double fertilization by twin sperm cells. Unlike animal germ lines, the male germ cell lineage in plants only forms after meiosis and involves asymmetric division of haploid microspores, to produce a large, non-germline vegetative cell and a germ cell that undergoes one further division to produce the twin sperm cells. Although this switch in cell cycle control is critical for sperm cell production and delivery, the underlying molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
201
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(218 citation statements)
references
References 37 publications
8
201
4
Order By: Relevance
“…However, all ICK/KRPs tested so far in overexpression studies can block both M and S phases (Verkest et al, 2005b), and at least KRP6 and KRP7 appear to be degraded at the G1/S transition point mediated by a CRL (cullin-RING ligase)-FBL17 complex (Kim et al, 2008;Gusti et al, 2009). By contrast, SIM expression appears to be compatible with DNA replication and preferentially represses M phase (Churchman et al, 2006;Peres et al, 2007).…”
Section: Control Of Mitotic Entry In Plantsmentioning
confidence: 99%
“…However, all ICK/KRPs tested so far in overexpression studies can block both M and S phases (Verkest et al, 2005b), and at least KRP6 and KRP7 appear to be degraded at the G1/S transition point mediated by a CRL (cullin-RING ligase)-FBL17 complex (Kim et al, 2008;Gusti et al, 2009). By contrast, SIM expression appears to be compatible with DNA replication and preferentially represses M phase (Churchman et al, 2006;Peres et al, 2007).…”
Section: Control Of Mitotic Entry In Plantsmentioning
confidence: 99%
“…For male germline development, a regulatory framework for cell cycle progression and gamete specification has been established Borg and Twell, 2010;Twell, 2011). Timely progression of the generative cell cycle requires the control of cyclin-dependent kinase activity by the F-box protein FBL17, which targets cyclin-dependent kinase inhibitory proteins for degradation (Kim et al, 2008;Gusti et al, 2009). In parallel, the male germline-specific MYB transcription factor DUO POLLEN1 (DUO1) integrates division of the generative cell with differentiation of the sperm cells (Rotman et al, 2005;Brownfield et al, 2009a;Borg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of cell cycle inhibitors by SCF FBL17 E3 ubiquitin ligase has been shown to control twin sperm-cell production. 16 Recent studies have demonstrated that degradation of repressors by SCFs through the ubiquitin-proteasome pathway plays a key role in plant hormone auxin, jasmonate, gibberellin, ethylene and abscisic acid signaling. 17,18 Circadian clock and photomorphogenesis are also regulated by proteasome-mediated protein degradation.…”
mentioning
confidence: 99%